Pengaruh Implementasi Sistem Pelayanan SITEK REBORN terhadap Kinerja Operasional PT Angkasa Pura Logistik Bandar Udara Ahmad Yani Semarang - Aditya Bagus Wicaksono; Fryda Fatmayati (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
In the era of globalization and increasingly fierce competition, logistics companies are required to improve the efficiency and effectiveness of their services. A good service system is one of the key factors in achieving this goal. The aim of the service system is expected to provide innovative solutions to improve the operational performance of officers, which includes aspects of speed, accuracy, and customer satisfaction through digitizing logistics services in the airport sector. The research aims to determine the effect of implementing the REBORN service system on the operational performance of PT Angkasa Pura Logistik officers at Ahmad Yani Airport, Semarang. This research uses quantitative methods. Primary data was collected through a questionnaire distributed to 40 respondents, consisting of operational officers at the PT Angkasa Pura Logistik Cargo Terminal. Samples were taken using a purposive sampling technique using the Isaac and Michael formula. Data was analyzed using SPSS 25 software with simple linear regression analysis, a T-test, and a coefficient of determination test. The research results show that the implementation of the SITEK REBORN system has a significant influence on the operational performance of PT Angkasa Pura Logistik. This is proven through a simple linear regression test, where the implementation variable shows a positive impact on the operational performance variable with a significance value of 0.000 < 0.05 and a t-count value of 9.268. In addition, the coefficient of determination (R²) of 0.693 indicates that 69.3% of the variation in operational performance can be explained by implementing the SITEK REBORN system. At the same time, the remainder is influenced by other variables not studied. This research concludes that digitalization through SITEK REBORN significantly improves operational performance, which in turn can increase the efficiency and productivity of PT Angkasa Pura Logistik at Ahmad Yani Airport, Semarang.